MENJAGA STABILITAS PENJUALAN DALAM UPAYA MENCAPAI STRUKTUR MODAL YANG OPTIMAL DI TENGAH PANDEMI COVID19 - Intan Elita (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2020)
This journal aims to find out the strategies used to maintain sales stability in an effort to achieve optimal capital structure in the middle of pandemic Covid-19. There is a relationship between sales stability and capital structure, if sales are relatively stable, the company can safely use higher debt and dare to bear a higher burden than sales that are relatively unstable. Strategy in the middle of pandemic Covid-19 companies need to reorganize strategies to be able to increase competition and be able to maintain sales stability, in the form of changes in corporate culture and strategies in marketing aspects.